"Our culture, how it is to be us" — Listening to Aboriginal women about on Country urban birthing. Issue 5 (October 2019) - Marriott, Rhonda; Reibel, Tracy; Coffin, Juli; Gliddon, Janinne; Griffin, Denese; Robinson, Melanie; Eades, Anne-Marie; Maddox, Jade
Abstract: Background: Birth on Country is often assumed as relevant to Aboriginal women in rural/remote locations and not usually associated with urban environments. In Western Australia, one third of the Aboriginal population live in the greater metropolitan area. We wanted to know Aboriginal women's experiences of on Country urban births. Methods: Indigenous qualitative data collection and analysis methods were used to learn about Aboriginal women's stories of contemporary and past experiences of maternity care and cultural practices associated with Birth on Country. Results: Aboriginal Birthing, Senior and Elder women consistently reported ongoing cultural practices associated with childbirth including knowledge sharing across generations and family support, observance of extended family present at the time of or shortly after birth, and how their cultural security was improved when Aboriginal staff were present. Also noted, were the inflexibility of health systems to meet their needs and midwives lack of cultural awareness and understanding of the importance of Aboriginal kinship. Conclusion: The Birthing on Noongar Boodjar project Aboriginal women's data represents four generations of women's stories, experiences and expressions of childbearing, which highlighted that maternity care changes across time have failed to acknowledge and support Aboriginal women's cultural needs during childbearing. In terms of on Country urban birth, the women collectively expressed a strong desire to maintain cultural practices associated with childbirth, including birthing close to home (on Country); having family acknowledged and included throughout the perinatal period; and, having access to Aboriginal midwives, nurses, doctors, and other health care workers to support their cultural security.